PENGARUH PENDIDIKAN, PENGALAMAN KERJA DAN JAM KERJA TERHADAP PENDAPATAN KARYAWAN DEPARTEMEN MAINTENANCE & UTILITIES PT. VALE INDONESIA TBK. - Theodorus Kristianto, Theodorus Kristianto (Fakultas Ekonomi Universitas 45 Surabaya, 2020)
This study aims to examine and analyze the Effects of Education, Work Experience and Working Hours on Employee Income of the Maintenance & Utilities Department of PT. Vale Indonesia Tbk .. Data collection was carried out through questionnaires and carried out on 120 people who were sampled in this study. Hypothesis testing uses analytical tools, namely multiple linear regression analysis, F-test, T-test and preceded by a classic assumption test. The results showed that the variable hours of work, work experience, and education had a simultaneous and significant effect on employee income at the Maintenance & Utilities Department of PT. Vale Indonesia Tbk and the variable hours of work, work experience, and education have a partial effect on employee income at the Maintenance & Utilities Department of PT. Vale Indonesia Tbk. T test results showed that it was concluded that education, work experience and working hours had a partial and positive effect on employee income at the Maintenance & Utilities Department of PT. Vale Indonesia Tbk. Thus it can be stated that education, work experience and working hours have a partial effect on the income of the employees of the Maintenance & Utilities Department of PT. Vale Indonesia Tbk. The results of data processing and simultaneous testing at a real level (a) = 5 percent shows that education, work experience and working hours have a simultaneous effect on the income of the Maintenance & Utilities Department of PT. Vale Indonesia Tbk. This is evident from the calculated F-value (100,848)> F table (2,708186). The magnitude of the influence of the three variables on employee income at the Maintenance & Utilities Department of PT. Vale Indonesia Tbk is indicated by Adjusted R Square = 0.767 which means that the income of the employees of the Maintenance & Utilities Department of PT. Through partial data processing results found that the variables of education, work experience, and working hours have a partial and positive effect on employee income at the Maintenance & Utilities Department of PT. Vale Indonesia Tbk. From this it is evident from the value of t-count each independent variable is greater than the value of t-table, where the education variable with t-count (3.261)> t-table (1.661585), while for the work experience variable with t-count ( 4,304)> t-table (1.66235) and variable hours worked with t-count (3.902)> t-table (1.66235